High-power AlGaN-based near-ultraviolet light-emitting diodes grown on Si(111). (26th June 2017) - Li, Zengcheng; Liu, Legong; Huang, Yingnan; Sun, Qian; Feng, Meixin; Zhou, Yu; Zhao, Hanmin; Yang, Hui
Abstract: High-power AlGaN-based 385 nm near-ultraviolet light-emitting diodes (UVA-LEDs) grown on Si(111) substrates are reported. The threading dislocation (TD) density of AlGaN was reduced by employing an Al-composition step-graded AlN/AlGaN multilayer buffer. V-shaped pits were intentionally incorporated into the active region to screen the carriers from the nonradiative recombination centers (NRCs) around the TDs and to facilitate hole injection. The light extraction efficiency was enhanced by the surface roughening of a thin-film (TF) vertical chip structure. The as-fabricated TF-UVA-LED exhibited a light output power of 960 mW at 500 mA, corresponding to an external quantum efficiency of 59.7%.